Analisis Kesadaran Hukum dalam Meminimalisir Potensi Tindak Pidana Penggelapan dan Penipuan di Kalangan Petani Padi : Studi Kasus di di Desa Taman, Kecamatan Jrengik, Sampang - Surya Nusantara; Sumriyah Sumriyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Crimes of embezzlement and fraud often occur among rice farmers, causing significant economic and social losses. This research aims to identify the factors that trigger these criminal acts and formulate effective prevention strategies. Through literature studies and in-depth interviews with farmers, extension officers, and law enforcement officials, this research found that a lack of legal knowledge, weak supervision, and unequal economic opportunities were the main factors. Based on these findings, this research suggests several preventive steps, such as increasing legal awareness, strengthening farmer institutions, and improving the harvest distribution system.